2015
DOI: 10.5397/cise.2015.18.4.248
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Scapular Notching after Reverse Total Shoulder Arthroplasty

Abstract: Background: Scapular notching can happen at diverse location depending on implant design or operative technique, therefore, it is easily misdiagnosed. Thus, this study purposed to suggest a method helpful to assess scapular notching. Methods: The subjects were 73 cases of reverse shoulder arthroplasty (RSA) for cuff tear arthropathy during the period from May 2009 to April 2014 and followed-up for over a year. There was medialized RSA in 22 cases, bone increased offset RSA (BIO-RSA) in 36 cases, and metal incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Age [12], obesity [13], status of the remained rotator cuff muscle [14,15], scapular notching [16,17], and lengthening of the lever arm[18] have been considered essential factors for clinical consequences subsequent to RTSA.…”
Section: Introductionmentioning
confidence: 99%
“…Age [12], obesity [13], status of the remained rotator cuff muscle [14,15], scapular notching [16,17], and lengthening of the lever arm[18] have been considered essential factors for clinical consequences subsequent to RTSA.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical course of scapular notching is debated [ 60 ]. Many studies have reported that patients without scapular notching showed better range of motion and functional outcomes than patients with scapular notching [ 57 , 60 ].…”
Section: Scapular Notchingmentioning
confidence: 99%
“…The clinical course of scapular notching is debated [ 60 ]. Many studies have reported that patients without scapular notching showed better range of motion and functional outcomes than patients with scapular notching [ 57 , 60 ]. Mollon et al [ 58 ] observed scapular notching with a single implant (medial glenoid/lateral humerus design) in 10% of 476 cases and found that patients with scapular notching showed poor functional scores, low degree of shoulder elevation, and reduced muscle strength [ 58 ].…”
Section: Scapular Notchingmentioning
confidence: 99%
“…On the AP (A), glenohumeral AP (B), and axillary lateral (C) views of x-rays performed 3-year after the surgery, scapular notching (arrow) is observed in the inferior and posterior aspects of the scapular neck. [1][2][3][4][5] On the axial (D), coronal (E), and 3D reconstruction (F) CT images performed 2 months after the surgery, it is evident that the lower 3 screws used for baseplate fixation are positioned closely within the narrow scapular vault, protruding through the far cortex (arrowhead). Such screw placement and scapular notching can potentially serve as stress risers.…”
mentioning
confidence: 99%
“…Although she initially experienced significant pain relief and had a favorable outcome for 2 years, she gradually complained of increasing pain from the third year onward. On the AP ( A ), glenohumeral AP ( B ), and axillary lateral ( C ) views of x-rays performed 3-year after the surgery, scapular notching (arrow) is observed in the inferior and posterior aspects of the scapular neck 1–5 . On the axial ( D ), coronal ( E ), and 3D reconstruction ( F ) CT images performed 2 months after the surgery, it is evident that the lower 3 screws used for baseplate fixation are positioned closely within the narrow scapular vault, protruding through the far cortex (arrowhead).…”
mentioning
confidence: 99%